2007
DOI: 10.1086/523598
|View full text |Cite
|
Sign up to set email alerts
|

Millimeter Interferometric HCN(1-0) and HCO+(1-0) Observations of Luminous Infrared Galaxies

Abstract: We present the results on millimeter interferometric observations of four luminous infrared galaxies (LIRGs), Arp 220, Mrk 231, IRAS 08572+3915, and VV 114, and one Wolf-Rayet galaxy, He 2Y10, using the Nobeyama Millimeter Array (NMA). Both the HCN(1Y0) and HCO + (1Y0) molecular lines were observed simultaneously, and their brightnesstemperature ratios were derived. High-quality infrared L-band (2.8Y4.1 m) spectra were also obtained for the four LIRGs to better constrain their energy sources deeply buried in d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
162
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(178 citation statements)
references
References 82 publications
14
162
2
Order By: Relevance
“…Line ratios of the dense gas tracers HCN, HNC, and HCO + have often been used in the literature to investigate the nature of the dominant energy source in LIRGs, either a compact starburst or an AGN (e.g., Imanishi et al 2007;Aalto et al 2007a;Krips et al 2008;Costagliola et al 2011).…”
Section: Standard Line Ratios: Hcn Hnc and Hco +mentioning
confidence: 99%
See 1 more Smart Citation
“…Line ratios of the dense gas tracers HCN, HNC, and HCO + have often been used in the literature to investigate the nature of the dominant energy source in LIRGs, either a compact starburst or an AGN (e.g., Imanishi et al 2007;Aalto et al 2007a;Krips et al 2008;Costagliola et al 2011).…”
Section: Standard Line Ratios: Hcn Hnc and Hco +mentioning
confidence: 99%
“…Line-ratio surveys have mostly focused on the brightest transitions of dense-gas tracers such as HCN, HNC, and HCO + , trying to compare the observed values to chemical models of photon-dominated regions (PDRs), X-ray dominated regions (XDRs), and hot-cores (e.g., Imanishi et al 2007;Loenen et al 2007;Krips et al 2008;Baan et al 2008;Costagliola et al 2011;Viti et al 2014). However, the line ratios of such bright tracers show only small variations and their theoretical interpretation is still controversial (e.g., Kohno et al 2001;Aalto et al 2007b;Meijerink et al 2007;Costagliola et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The dense molecular gas tracer HCN has been found to be enhanced (relative to HCO+ and CO) in systems with dominant AGNs (e.g., Imanishi et al 2007). Privon et al (2015) have shown that some pure starburst and composite sources show similarly enhanced HCN emission.…”
Section: Optical and Radio Emissionmentioning
confidence: 99%
“…At millimeter wavelengths, HCN has been found to be enhanced over HCO + in ULIRGs (Graciá-Carpio et al 2006) and in Seyferts over starbursts (Imanishi et al 2007), and this has been proposed to be a diagnostic of AGN activity. Costagliola et al (2011), however, argue that for high densities and columns HCO + is expected to be stronger than HCN in XDRs (Meijerink et al 2007).…”
Section: Model Uncertaintiesmentioning
confidence: 99%